Clinico-pathological Evaluation of Infection Pattern in Surgical Wards (The Planet, 2022)
Background: Infection in surgical patients is an ongoing process. Through the whole world, nosocomial infections are considered as hindrance in medical and surgical practice. In the present study, we have attempted to explore different clinical and microbiological aspect of infection in surgical patient. Objective: To find out the bacterial aetiology and the rate of post operative wound infections in relation with total number of infections. Method: This Descriptive cross-sectional observational study conducted among the Male and female wards and cabins under surgery unit.1 of Rangpur medical college hospital. Laboratory works were done in microbiology department of Rangpur medical college. Results: As per age and sex distribution, male were predominating with male to female ratio of 1.8:1,where majority cases(37%) were in the age group of 15-30 years; categorically, patient were divided into different groups (a) a group of 47 patients developed post operative wound infection, (b)another group of 42 patient admitted with prior infection, in all categories majority patient were in male general ward.Most of the infections either prior(47.2% ) or post-operative(52.8%)were local wound infections. Highest rate of post operative and prior infections was found in male general ward (30.33%) and 26.96% accordingly. Pre-morbidity statuses of our patients were recorded. Out of 3 patients with diabetes mellitus, 2 developed wound infections and out of 5 cases of malignancy only 2 developed wound infections. Clinically suspected cases of infection ewre evaluated by culture and sensitivity test. A total of 89 sample comprising as 59 wound swab, 24 pus, 4urine and 2 blood. Growth of organisms were noted in 43 samples of which pseudomonas ssp. was highest (16) followed by esch.coli (15) and staph.aureus (08).Pseudomonas ssp. Isolated from patients was highly sensitive to cetazidime and atreonam (>93%).Resistance to ciprofloxacine, pefloxacine,gentamicine and ceftriaxoneewre 31.2%, 28.6%, 50.0% and 12.5% respectively. In 37.5%strains, ceftriaxone showed intermediate sensitive pattern. Esch.coli isolated from patients were 100% resistant to amoxicillin followed by 71.4% to doxycycline and 64.3% to cotrimoxazole. Over 57% strain were resistant to gentamicin and cephalexin. Ciprofloxacin was sensitive in 71.4% and ceftriaxone in 65.3%. Here also 24.3% strain showed intermediate sensitive pattern against ceftriaxone. Staph.aureus strains were highly sensitive to cloxacillin, erythromycin, cephradine, ciprofloxacin, doxycycline, and gentamicin. But penicillin and cotrimoxazole were highly resistant. Conclusion: After analyzing the data of the current study, it was concluded that, despite having practically all of the risk factors for nosocomial infection, the rate can be reduced if sufficient attention is given before, after, and during the surgery. Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus remain nosocomial pathogens. Most nosocomial bacteria are still very sensitive to third-generation cephalosporins, such as ceftriaxone and ceftazidime, as well as azteonam. Antibiotics should not be used at random in surgical patients due to the emergence of a significant number of intermediate sensitive strains that run back to the side of resistance.
Keywords: Nosocomial infections; post-operative infection; bacterial aetiology